INVENTORY CONTROL OF DISPOSABLE MEDICAL MATERIALS AT THE BALI MANDARA EYE HOSPITAL - Ni Wayan Yuli Yudianti; Putu Nina Eka Lestari; Gde Sri Darma; IB Raka Suardana (Indonesian Journal of Health Administration, 2021)
Background: As a health service institution, hospitals have characteristics and management complexities which have an impact on their financing aspects. Controlling the supply of pharmaceutical supplies aims to create a balance between supply and demand in order to realize effective and efficient health services.Aims: This study aimed to design a method for controlling the optimal supply of disposable medical materials at the Bali Mandara Eye Hospital, Bali. Methods: This is a qualitative study based on in-depth interviews with three informants, and involving 11 doctors (users) to determine the critical value of disposable medical materials.Results: ABC analysis was used to classify all types of goods based on their importance to determine priorities based on the value of use. The budget allocation was dominated by only a small portion or only a few types of pharmaceutical supplies. The results show that there was a decrease in the total cost of inventory by 19.14% after the application of the EOQ method. The application of the reorder point (ROP) method can anticipate the occurrence of stock outs or vacancies.Conclusion: The EOQ method is more efficient than the conventional method applied at the Bali Mandara Eye Hospital Pharmacy Installation. The EOQ and ROP methods greatly affect the efficiency and effectiveness of controlling the inventory of medical disposable materials at the Bali Mandara Eye Hospital.Keywords: : inventory control, effective and efficient, medical disposable materials